Extended Reality Technologies for Sustainable Development of Learning and Education in Indonesia - Yudhistyra, Wecka Imam; Rosyidah, A'Liyatur; Srinuan, Chalita; Chaveesuk, Singha (My University, 2022)
The development of Extended Reality (XR) technologies has reached a new advanced level today, which could be proposed as the main support in solving education problems in Indonesia. As a result, this manuscript seeks to provide an initial framework to support the idea of suggesting the most recent XR technologies as primary instruments in promoting the Sustainable Development of Learning and Education (SDLE). Based on the literature review, the old but gold Technology Acceptance Model (TAM) framework is extended with several constructs in proposing this initial framework. Several constructs proposed in this initial proposed framework are Perceived Easy-of-Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), Intention to Use (ITU), User Satisfaction (US), Learner Flexibility (LF), Self-Efficacy (SF), and Perceived Health Risk (PRH). Certainly, further research is needed to assess and determine the validity of this preliminary framework in order to serve as a guide for scientists, experts, and other stakeholders interested in integrating XR technologies for SDLE.
Keywords: Augmented Reality (AR); Extended Reality (XR); Sustainable Development of Learning and Education (SDLE); Virtual Reality (VR)